The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/mbio.00949-16
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Constraints of Cyanobacterial Productivity: Acclimations Enabling Ultrafast Growth

Abstract: Harnessing the metabolic potential of photosynthetic microbes for next-generation biotechnology objectives requires detailed scientific understanding of the physiological constraints and regulatory controls affecting carbon partitioning between biomass, metabolite storage pools, and bioproduct synthesis. We dissected the cellular mechanisms underlying the remarkable physiological robustness of the euryhaline unicellular cyanobacterium Synechococcus sp. strain PCC 7002 (Synechococcus 7002) and identify key mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 63 publications
(79 reference statements)
1
40
0
Order By: Relevance
“…Such observations, together with cultivation experiments using organic acids, indicated that the TCA cycle and its associated anabolic pathways in Synechococcus 2973 operate at lower rates than in E. coli , which would limit production of chemicals from the cyanobacterial TCA cycle [ 4 ]. In Synechococcus 2973, the photosynthetic capacity generates sugar phosphates readily (FBP phosphatase/aldolase, fructose-bisphosphatase, transketolase, and RuBisCO reactions) that can enhance its growth [ 31 33 ] and could potentially be applied for biotechnological productions [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such observations, together with cultivation experiments using organic acids, indicated that the TCA cycle and its associated anabolic pathways in Synechococcus 2973 operate at lower rates than in E. coli , which would limit production of chemicals from the cyanobacterial TCA cycle [ 4 ]. In Synechococcus 2973, the photosynthetic capacity generates sugar phosphates readily (FBP phosphatase/aldolase, fructose-bisphosphatase, transketolase, and RuBisCO reactions) that can enhance its growth [ 31 33 ] and could potentially be applied for biotechnological productions [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of the plasmid in the absence of antibiotic selection was assayed based on the shuttle vector maintenance protocol in Syn7942 with some minor modifications ( Chen et al, 2016b ). The test was conducted at a similar stage (1-week-old cultures) because Syn6803 and Syn7942 have similar doubling times (between 7 and 12 h) ( Bernstein et al, 2016 ). Cells with pSCB-YFP were grown in medium supplemented with Sp 10 μg/ml for 7 days, then inoculated into two flasks, each containing 50 ml of medium, one containing 10 μg/ml Sp, the other without antibiotic.…”
Section: Methodsmentioning
confidence: 99%
“…We used time-lapse fluorescence microscopy to track fluorescently labeled carboxysomes in single Synechococcus sp. PCC 7002 (hereafter PCC 7002) cells, chosen for their fast growth rate (13) and industrial relevance (14)(15)(16). Unlike bulk culture techniques, microscopy enables analysis of individual carboxysomes and has been used to describe carboxysome organization within the cell (17,18).…”
Section: Introductionmentioning
confidence: 99%